How does industrial policy experimentation influence innovation performance? A case of Made in China 2025 - Kejing Chen; Qiaoshuang Meng; Yutao Sun; Qingqing Wan (Humanities & Social Sciences Communications, 2024)
Abstract Made in China 2025 (MIC 2025), an industrial policy, aims to position China among the global leading manufacturing powers. Different from other industrial policies in China, MIC 2025 is implemented by policy experimentation of pilot cities, which gives priority to the local governments. However, whether MIC 2025 pilot cities promote firm innovation is unclear in current literature. Using MIC 2025 pilot cities as a quasi-natural experiment, this study analyzes the effect and the mechanism of MIC 2025 on firm innovation. The sample consists of 4422 firm-year observations of Chinese listed manufacturing firms in 2012–2022. The result indicates that focal firm located in MIC 2025 pilot cities facilitates its innovation. Mechanism analysis show that MIC 2025 promotes firm innovation through tax incentives, public subsidies, convenient financing, academic collaboration and talent incentives. This study extends industrial policy literature with regard to how place-based policy experimentation promote the implementation of China’s industrial policies. Local governments’ participations and their interaction with the central government are vital for a successful policy experimentation.